علم النص: تحريات في دلالة النص و تداوله - لحلوحي, فهيمة (Revues faculté des lettres et des langues; No 10-11 (2012): مجلة كلية الآداب واللغات, 2014)
لقد شهدت أواخر الستينيات وبداية السبعينيات تطورا ملحوظا في ميدان الدرس اللساني الحديث نتج عنه ميلاد فرع معرفي جديد عرف باسم علم النص، وموضوعه الأساسي هو النص بوصفه أعلى وحدة لغوية في الدراسات النصية. يهدف هذا العمل إلى استقصاء بعض إشكاليات مصطلح النص وعلم النص؛ من حيث تعدد مصطلحاتهما وتشعب تعريفاتهما. بالإضافة إلى التعرض إلى اتجاهاته وأسسه المعرفية.   The late sixties and early seventies had witnessed a rapid development in modern linguistics, which led to the rise of a new trend called "Text Linguistics". As the term itself implies, the text, which is considered as the ultimate language unit, is the main focus and subject matter of this discipline. This study aims at the systematic exploration of the controversies over text linguistics as well as the variety of its key terms, definitions, and notions. Simultaneously, we intend to touch on the major currents and basics of text linguistics